2014
DOI: 10.3945/ajcn.113.067488
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium intake, bone mineral density, and fractures: results from the Women’s Health Initiative Observational Study

Abstract: Lower magnesium intake is associated with lower BMD of the hip and whole body, but this result does not translate into increased risk of fractures. A magnesium consumption slightly greater than the Recommended Dietary Allowance is associated with increased lower-arm and wrist fractures that are possibly related to more physical activity and falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(135 citation statements)
references
References 42 publications
8
110
0
4
Order By: Relevance
“…However, a recent US study (7) of postmenopausal women found no difference in relative risk of hip and total fractures across quintiles of magnesium intake. Conversely, high magnesium intake ($422.5 mg/d) was associated with increased falls and wrist or lower arm fractures (7). By contrast, our analyses show a statistically significant reduction in hip fracture risk with moderately high (206-442 mg/d; quintile 4) combined magnesium and potassium intakes and no significant increases in risk of wrist fracture in either men or women in fully adjusted models, although it is acknowledged that the 95% CIs for wrist fracture risk are wide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent US study (7) of postmenopausal women found no difference in relative risk of hip and total fractures across quintiles of magnesium intake. Conversely, high magnesium intake ($422.5 mg/d) was associated with increased falls and wrist or lower arm fractures (7). By contrast, our analyses show a statistically significant reduction in hip fracture risk with moderately high (206-442 mg/d; quintile 4) combined magnesium and potassium intakes and no significant increases in risk of wrist fracture in either men or women in fully adjusted models, although it is acknowledged that the 95% CIs for wrist fracture risk are wide.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of magnesium and potassium is linked because magnesium is required for effective Na + /K + -ATPase pump function (17), magnesium and potassium have additive effects in preventing an increase in the endogenous sodium potassium pump inhibitor (16), and both have direct and indirect effects on calcium homeostasis (9,18). Previous studies of the association of dietary magnesium and potassium with bone health have had limited generalizability because of their focus on discrete population groups, such as narrow age range groups of relatively old (5,19) or young individuals (20), restrictions to premenopausal (8,20) or postmenopausal women only (13), and non-United Kingdom residents (5,7,20). Indeed, the most recent and comprehensive study, with a large cohort size and longitudinal analysis of fracture risk, was also limited to women only (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary and serum, but not red cell, magnesium were generally lower among the elderly with osteoporosis 45,86,109 and among healthy older adults, magnesium intake was positively associated with BMD, BMC and bone mass 86,[110][111] , with an intake of >422.5mg/d vs <206.5 mg/d improving BMD 110 . A large multiethnic study found that this association may apply to older whites but not blacks 112 .…”
Section: Bonementioning
confidence: 99%
“…Some studies also found an association with BMD in younger women [113][114] . Study results are mixed with respect to intake and fracture risk 84,110,115 and among Japanese subjects low serum magnesium was associated with increased fracture incidence 116 . Short term intervention studies Mechanism by which high serum phosphate (P) impacts the parathyroid gland and kidney to lower serum P…”
Section: Bonementioning
confidence: 99%